miR-aculous new avenues for cancer immunotherapy - Tang, William W.; Bauer, Kaylyn M.; Barba, Cindy; Ekiz, Huseyin Atakan; O’Connell, Ryan M. (Frontiers in Immunology, 2022)
The rising toll of cancer globally necessitates ingenuity in early detection and therapy. In the last decade, the utilization of immune signatures and immune-based therapies have made significant progress in the clinic; however, clinical standards leave many current and future patients without options. Non-coding RNAs, specifically microRNAs, have been explored in pre-clinical contexts with tremendous success. MicroRNAs play indispensable roles in programming the interactions between immune and cancer cells, many of which are current or potential immunotherapy targets. MicroRNAs mechanistically control a network of target genes that can alter immune and cancer cell biology. These insights provide us with opportunities and tools that may complement and improve immunotherapies. In this review, we discuss immune and cancer cell-derived miRNAs that regulate cancer immunity and examine miRNAs as an integral part of cancer diagnosis, classification, and therapy.